Genomic characterization and antimicrobial activity of Pediococcus pentosaceus ST65ACC - Oliveira, Francielly Soares (2023)
The bacteriocinogenic strain Pediococcus pentosaceus ST65ACC was previously isolated from Brazilian artisan cheese (BAC) and showed strong bactericidal activity against Listeria monocytogenes. This strain also showed beneficial properties, such as the ability to survive gastrointestinal conditions and to aggregate with L. monocytogenes, indicating it as a potential probiotic candidate. The present study aimed to genomically characterize the P. pentosaceus ST65ACC strain through whole-genome sequencing (WGS), analyzing its technological and beneficial properties, bacteriocin clusters, and safety profiles, and also evaluating its antimicrobial activity against L. monocytogenes Scott A in different culture media. The genome of P. pentosaceus ST65ACC comprises 1,933,194 bp witha GC content of 37.00 %, and contains1,950 protein coding sequences (CDSs) with 62 RNA genes (6 rRNA, 55 tRNA, 1 tmRNA). Genomic analysis revealed the presence of operons that encode the bacteriocins pediocin PA-1/AcH and penocin-A, and also identified the presence of genes related to beneficial properties, such as stress adaptation genes and adhesion genes. Regarding the strain safety profiles, genes encoding biogenic amines and virulence genes were not detected. Genes related to antibiotic resistance were identified in the genome, but not in prophage regions, and no plasmids were detected, thus presenting a low risk of transferring to other bacteria. The results obtained fromthe interaction of P. pentosaceus ST65ACC and L. monocytogenes Scott A in MRS broth, BHI broth, milk, and meat broth for 96 h showed that the antimicrobial activity of the strain was more effective in MRS broth. L. monocytogenes was inhibited toun detectable levels by the strain in MRS broth during the 96 h of analysis, with high levels of bacteriocin production (3,200 – 12,800 AU/ml) being identified. However, lower inhibitory activities were recorded in BHI, milk, and meat broth, with low or no production of bacteriocins at the times analyzed. Thus, verifying that the composition of the media can interfere with the production/activity of bacteriocins and, consequently, with the antagonistic activity of P. pentosaceus ST65ACC on L. monocytogenes Scott A. The results obtained through genomic characterization confirmed the beneficial potential and safety of P. pentosaceus ST65ACC, indicating that this strain can be considered suitable for application in food biopreservation, as well as a promising probiotic candidate. Keywords: Pediococcus. Biopreservation. Bacteriocins. Pediocin. Genomic analysis.